Associations of menstrual health with school absenteeism and examination performance among Ugandan secondary school students: A prospective study - Christopher Baleke; Levicatus Mugenyi; Kate A. Nelson; Katherine A. Thomas; Denis Ndekezi; Jonathan Reuben Enomut; Connie Alezuyo; John Jerrim; Helen A. Weiss (PLoS ONE, 2026)
Background Relatively few studies have quantified the amount of school missed due to poor menstrual health, or the impact of poor menstrual health on examination performance. Methods We conducted secondary observational analyses from data nested within a cluster-randomised trial of a menstrual health intervention in 60 Ugandan secondary schools (The trial is registered as ISRCTN45461276). We used baseline data from trial participants in both arms, and endline data from the control arm participants. School absenteeism was estimated as the self-reported number of days absent due to menstruation per month and examination performance was assessed by an independently set assessment by the Uganda National Examination Board. We estimated adjusted incidence rate ratios (aIRR) for associations with school absenteeism, using negative binomial regression adjusted for school-level clustering. We estimated adjusted standardised mean differences (aSMD) in examination scores using mixed-effects linear regression. Results Of the 3312 participants who reported menstruating in the past 6 months at baseline, 323 (9.8%) reported missing at least one day of school per month due to menstruation (mean days missed = 0.30 per month, 95%CI 0.27–0.34). Similarly, of the 1192 participants in the trial control arm seen at endline, 135 (11.3%) reported missing at least one day due to menstruation (mean days missed = 0.31 per month (95%CI 0.27–0.37)). There was evidence that menstrual-related absenteeism and poorer examination performance at endline were both associated with baseline use of inadequate menstrual materials, negative menstrual attitudes, unmet menstrual practice needs, and experience of menstrual-related teasing. In addition, absenteeism due to menstruation was associated with menstrual pain, and poorer examination performance was associated with poorer baseline menstrual knowledge. Conclusion Among Ugandan students, multiple dimensions of menstrual health are associated with school absenteeism and examination performance. Trial registration and recruitment details ISRCTN ISRCTN45461276 .